Emotional neglect and prosocial behavior among left-behind youth in China: roles of resilience and family socioeconomic status - Ronghua Zhang; Ying Luo; Chunmei Zhang (Acta Psychologica)
Previous research has revealed that left-behind children—those under 18 whose parents have migrated for work for a period of six months or more, leaving them behind in their hometown—face higher levels of emotional neglect. This neglect primarily exacerbates negative psychological outcomes. However, its adverse effects on positive psychological functioning, such as resilience and prosocial behavior, in left-behind youth have not been fully explored. This study aims to explore factors that mitigate the impact of emotional neglect on developmental outcomes, specifically examining how resilience protects against emotional neglect and promotes prosocial behavior. Additionally, the study considers the distinct influence of family socioeconomic status on these relationships. The study involved 975 youth participants: 370 left-behind youth (Mage = 17.96, 51.4 % female) and 605 non-left-behind youth (Mage = 18.08, 49.1 % female), all from various regions in China. All participants completed a face-to-face questionnaire administered in a computer room at their respective school. The Results indicated that: (a) Left-behind youth exhibited higher levels of emotional neglect compared to non-left-behind youth, while resilience and prosocial behavior did not significantly differ between the groups. (b) Emotional neglect showed a significant negative correlation with prosocial behavior. (c) Resilience significantly mediated the relationship between emotional neglect and prosocial behavior, with a mediating effect size of 57.45 %. (d) Family socioeconomic status significantly moderated this relationship. Specifically, individuals from lower SES families exhibited more prosocial behavior when experiencing lesser degrees of emotional neglect. This study provides novel insights into the mechanism of emotional neglect on prosocial behavior among Chinese left-behind youth, highlighting the pivotal role of resilience and family socioeconomic status.